STUDI FENOMENOLOGI KEBUTUHAN DAN HAMBATAN PERAWAT DALAM PELAKSANAAN RESUSITASI PADA KEGAWATAN NEONATUS PREMATUR DI RUANG NEONATUS RSD DR. HARYOTO LUMAJANG - Arista Maisyaroh* Retty Ratnawati** Septi Dewi Rachmawati*** (Universitas Muhammadiyah Jember, 2015)
Clinical Nurses must have competence in the treatment of patients with emergency conditions, including the resuscitation in preterm neonates. But in practice many needs and obstacle in order to achieve the best quality of resuscitation. Personal abilities and limitations of the equipment could become an obstacle in the implementation of resuscitation, besides that nurses also require upgrading of competence to be able to improve the quality of resuscitation. But in fact the nurse experience in this regard is still not much explored. The research objective is to explore the needs and obstacle of nurses in performing resuscitation on critical of preterm neonates in neonatal ward of RSD Dr Haryato Lumajang The study design used is qualitative interpretative phenomenological approach . in-depth interviews using semi-structured questions involving 7 nurses neonatal ward RSD Dr Haryato Lumajang. Data were collected and analyzed using thematic analysis approach based Braun Clarke.This study resulted in five themes, namely personal challenge, the complexity of organizing the team, limited facilities, improving the competence and adequacy of equipment.The results of the overall interview participants showed that resuscitation is not only an individual act but a dynamic team organization, so that barriers resuscitation implementation not only of personal helper but also of organizing the resuscitation team backed by equipment needs to improve the quality of resuscitation. To reduce existing barriers can be done to increase the competence helper with periodic refresher training and to increase the perception among the team members so as to improve the quality of the team organization resuscitation.